Bayesian Filtering in Incoherent Scatter Plasma Parameter Fits. Issue 3 (22nd March 2021) - Virtanen, Ilkka I.; Tesfaw, Habtamu W.; Roininen, Lassi; Lasanen, Sari; Aikio, Anita
Abstract: Incoherent scatter (IS) radars are invaluable instruments for ionospheric physics, since they observe altitude profiles of electron density ( N e ), electron temperature ( T e ), ion temperature ( T i ) and line‐of‐sight plasma velocity ( V i ) from ground. However, the temperatures can be fitted to the observed IS spectra only when the ion composition is known, and resolutions of the fitted plasma parameters are often insufficient for auroral electron precipitation, which requires high resolutions in both range and time. The problem of unknown ion composition has been addressed by means of the full‐profile analysis, which assumes that the plasma parameter profiles are smooth in altitude, or follow some predefined shape. In a similar manner, one could assume smooth time variations, but this option has not been used in IS analysis. We propose a plasma parameter fit technique based on Bayesian filtering, which we have implemented as an additional Bayesian Filtering Module (BAFIM) in the Grand Unified Incoherent Scatter Design and Analysis Package (GUISDAP). BAFIM allows us to control gradients in both time and range directions for each plasma parameter separately. With BAFIM we can fit F1 region ion composition together with N e, T e, T i and V i, and we have reached 4 s/900 m time/range steps in four‐parameter fits of N e, T e, T i and V i in E region observations of auroral electron precipitation. Key Points: Full‐profile incoherent scatter analysis is implemented by means of Bayesian filtering and correlation priors The technique reaches high time resolutions and enables ion composition fits We have implemented the technique as an additional module to the Grand Unified Incoherent Scatter Design and Analysis Package (GUISDAP) incoherent scatter analysis tool